1992
DOI: 10.1111/j.1472-765x.1992.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced acid tolerance in Listeria monocytogenes

Abstract: Growth of Listeria monocytogenes at pH 5·0 did not increase growth of the organism at pH 7·0 after exposure to low pH (3·0, 3·5), compared with cells initially grown at pH 7·0. However, growth at pH 5·0 significantly increased the survival of cells at low pH as determined by plate counts compared with cells grown at neutral pH. Thus, pH adaptation not only occurs in enteric bacteria but also in this Gram‐positive organism. Alterations in the cytoplasmic membrane could be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 10 publications
5
78
1
Order By: Relevance
“…At pH 3, no surviving bacteria were detectable after 1 h of challenge. At pH 3 (HCl) with rich media, however, we (results not shown) and other authors (Davis et al, 1996;Kroll and Patchett, 1992) have observed the survival of L. monocytogenes after 1 h of acid challenge. The main reason for this disparity lies in the media used.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…At pH 3, no surviving bacteria were detectable after 1 h of challenge. At pH 3 (HCl) with rich media, however, we (results not shown) and other authors (Davis et al, 1996;Kroll and Patchett, 1992) have observed the survival of L. monocytogenes after 1 h of acid challenge. The main reason for this disparity lies in the media used.…”
Section: Discussioncontrasting
confidence: 44%
“…Some physiological aspects of acid tolerance in L. monocytogenes in rich media have also been reported (Farber and Pagotto, 1992;Gahan et al, 1996;Kroll and Patchett, 1992;O'Driscoll et al, 1996). Rich and complex media such as brain heart infusion (BHI) broth or tryptic soy broth supplemented with yeast extract support better bacterial growth than minimal media do (Phan-Thanh and Gormon, 1997), but they are variable in composition and contain protecting substances susceptible of attenuating the effects of pH.…”
mentioning
confidence: 85%
“…Little is known about the acquisition of acid tolerance by L. monoytugenes. One preliminary report demonstrated that L. monoytogenes showed increased survival at pH 3.0 when first grown at an acidic pH (Kroll & Patchett, 1992). This study demonstrated that a culture of L. monoytugenes grown at pH 5.0 survived well when challenged at pH 3.0 compared to a culture grown at pH 7.0 prior to the challenge.…”
Section: Introductionmentioning
confidence: 65%
“…monocytogenes can induce a protein synthesis-dependent log-phase ATR when exposed to an induction pH (5.0 to 5.5), dramatically increasing the resistance of log-phase cells (69,135,170) to more extreme acidic conditions. One of the primary consequences of acid adaptation appears to be an increased intracellular pH (pH i ), since it was found that at low external pH, acid-adapted and acid-resistant mutant cells maintained an elevated pH i relative to the wild type.…”
Section: Listeria Monocytogenesmentioning
confidence: 99%